60 days to a greener life : ease eco-anxiety through joyful daily action - White, Heather (Harper Horizon, 2024)
"Do you want to make eco-friendly choices, but you don't know how? Are you worried about the climate crisis? Do you want to help but aren't sure where to start? 60 Days to a Greener Life offers impactful ideas for adjusting your lifestyle with the environment in mind. Each entry in this easy-to-implement guide includes insight on a green-related topic and an energizing prompt or resource about turning eco-friendly practices into joy-filled habits."--